ANALISIS DAYA SAING USAHATANI KELAPA SAWIT DI KABUPATEN MUKOMUKO (STUDI KASUS DESA BUMI MULYA) - Aprizal, Aprizal; Asriani, Putri Suci; Sriyoto, Sriyoto (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
This study aimed to analyze the competitiveness of palm oil farming (competitive and comparative advantage), the impact of government policies on output and input oil palm cultivation, and the competitiveness of sensitivity to changes in oil palm farm output and input. Stratified Random Sampling method was used to select 86 respondents purposively. The reason for choosing of Mukomuko district is because this area has largest palm oil producers and largest palm oil planting area in the province of Bengkulu. The data used primary and secondary data. The Policy Analysis Matrix (PAM) method was used to analyze the data. The result shows that Bumi Mulya Village has competitive and comparative advantages. PP and SP have positive value of PCR (0,91), and DRCR (0,72). The impact of government policy on output are disincentive as shown by OT value negative Rp.5.521.890/Ha/year, value NPCO is 0,80. The impact of government policy subsidy to input is fertilizer. NT has negative value, EPC is 0,80, and SRP about 0,166. Government policy shows that the fertilizer is still needed on palm oil farming. The sensitivity analysis shows that the maximum limit that can be accepted to change the output when the input-output and prices drop below 3 percent, price increases of more than 100 percent of herbicides, inorganic fertilizer price increases below 55 percent, rising interest rates below 1 percent. Combination of sensitivity analysis shows that the fluctuation in input-output is very sensitive to oil palm farming in Bumi Mulya, Mukomuko district.